Syair Tionghua peranakan Indonesia - Low, Kok On (Universiti Kebangsaan Malaysia, 2003)
Peranakan Chinese is considered a unique ethnic group in Indonesia due to assimilation of Malay culture into theirs. They used bahasa baba which is sometimes called Melayu in their daily conversation as well as in writing. It is through it that the Peranakan Chinese has produced amazingly a great deal of traditional Malay poems, namely the pantun and syair. This report deals with the identity and beauty of peranakan Chinese syair published in the 19th Century